69.1k views
0 votes
I need help with these removable discontinuities.


I need help with these removable discontinuities. ​-example-1

1 Answer

0 votes

Answer:

First problem: a (2,0)

Second problem: b. none of these; the answer is (4, 5/3) which is not listed.

Third problem: b. none of the above; there are no holes period.

Explanation:

First problem: The hole is going to make both the bottom and the top zero.

So I start at the bottom first.


x^2-3x+2=0

The left hand expression is factorable.

Since the coefficient of
x^2 is 1, you are looking for two numbers that multiply to be 2 and add to be -3.

Those numbers are -2 and -1 since (-2)(-1)=2 and -2+(-1)=-3.

The factored form of the equation is:


(x-2)(x-1)=0.

This means x-2=0 or x-1=0.

We have to solve both equations here.

x-2=0

Add 2 on both sides:

x=2

x-1=0

Add 1 on both sides:

x=1

Now to determine if x=2 or x=1 is a hole, we have to see if it makes the top 0.

If the top is zero when you replace in 2 for x, then x=2 is a hole.

If the top is zero when you replace in 1 for x, then x=1 is a hole.

Let's do that.


x^2-4x+4

x=2


2^2-4(2)+4


4-8+4


-4+4


0

So we have a hole at x=2.


x^2-4x+4

x=1


1^2-4(1)+4


1-4+4


-3+4


1

So x=1 is not a hole, it is a vertical asymptote. We know it is a vertical asymptote instead of a hole because the numerator wasn't 0 when we plugged in the x=1.

So anyways to find the point for which we have the hole, we will cancel out the factor that makes us have 0/0.

So let's factor the denominator now.

Since the coefficient of
x^2 is 1, all we have to do is find two numbers that multiply to be 4 and add up to be -4.

Those numbers are -2 and -2 because -2(-2)=4 and -2+(-2)=-4.


f(x)=((x-2)(x-2))/((x-2)(x-1))=(x-2)/(x-1)

So now let's plug in 2 into the simplified version:


f(2)=(2-2)/(2-1)=(0)/(1)=0.

So the hole is at x=2 and the point for which the hole is at is (2,0).

a. (2,0)

Problem 2:

So these quadratics are the same kind of the ones before. They all have coefficient of
x^2 being 1.

I'm going to start with the factored forms this time:

The factored form of
x^2-3x-4 is
(x-4)(x+1) because -4(1)=-3 and -4+1=-3.

The factored form of
x^2-5x+4 is
(x-4)(x-1) because -4(-1)=4 and -4+(-1)=-5.

Look at
((x-4)(x+1))/((x-4)(x-1)).

The hole is going to be when you have 0/0.

This happens at x=4 because x-4 is 0 when x=4.

The hole is at x=4.

Let's find the point now. It is (4,something).

So let's cancel out the (x-4)'s now.


(x+1)/(x-1)

Plug in x=4 to find the corresponding y:


(4+1)/(4-1){/tex]</p><p>[tex](5)/(3)

The hole is at (4, 5/3).

Third problem:


x^2-4x+4 has factored form
(x-2)(x-2) because (-2)(-2)=4 and -2+(-2)=-4.


x^2-5x+4 has factored form
(x-4)(x-1) because (-4)(-1)=4 and -4+(-1)=-5.

There are no common factors on top and bottom. You aren't going to have a hole. There is no value of x that gives you 0/0.

User Alekya Reddy
by
5.1k points